Trajectories of response to acupuncture for menopausal vasomotor symptoms: the Acupuncture in Menopause study. Issue 2 (February 2017) - Avis, Nancy E.; Coeytaux, Remy R.; Levine, Beverly; Isom, Scott; Morgan, Timothy
Abstract: Objective: To examine the trajectories of responses to acupuncture treatment for menopausal vasomotor symptoms (VMS) and the characteristics of women in each trajectory. Methods: Two hundred nine perimenopausal and postmenopausal women aged 45 to 60 years experiencing at least four VMS per day were recruited and randomized to receive up to 20 acupuncture treatments within 6 months or to a waitlist control group. The primary outcome was percent change from baseline in the mean daily VMS frequency. Finite mixture modeling was used to identify patterns of percent change in weekly VMS frequencies over the first 8 weeks. The Freeman-Holton test and analysis of variance were used to compare characteristics of women in different trajectories. Results: Analyses revealed four distinct trajectories of change in VMS frequency by week 8 in the acupuncture group. A small group of women (11.6%, n = 19) had an 85% reduction in VMS. The largest group (47%, n = 79) reported a 47% reduction in VMS frequency, 37.3% (n = 65) of the sample showed only a 9.6% reduction in VMS frequency, and a very small group (4.1%, n = 7) had a 100% increase in VMS. Among women in the waitlist control group, 79.5% reported a 10% decrease in VMS frequency at week 8. Baseline number of VMS, number of acupuncture treatments in the first 8 weeks, and traditional Chinese medicine diagnosis were significantly related to trajectory group membership in the acupuncture group. Conclusions: Approximately half of the treated sample reported a decline in VMS frequency, but identifying clear predictors of clinical response to acupuncture treatment of menopausal VMS remains challenging.